Geospatial, Clinical, and Social Determinants of Hospital Readmissions. (November 2019) - Ye, Yun; Beachy, Micah W.; Luo, Jiangtao; Winterboer, Tammy; Fleharty, Brandon S.; Brewer, Charlotte; Qin, Zijian; Naveed, Zaeema; Ash, Michael A.; Baccaglini, Lorena
Unnecessary hospital readmissions increase patient burden, decrease health care quality and efficiency, and raise overall costs. This retrospective cohort study sought to identify high-risk patients who may serve as targets for interventions aiming at reducing hospital readmissions. The authors compared geospatial, social demographic, and clinical characteristics of patients with or without a 90-day readmission. Electronic health records of 42 330 adult patients admitted to 2 Midwestern hospitals during 2013 to 2016 were used, and logistic regression was performed to determine risk factors for readmission. The 90-day readmission percentage was 14.9%. Two main groups of patients with significantly higher odds of a 90-day readmission included those with severe conditions, particularly those with a short length of stay at incident admission, and patients with Medicare but younger than age 65. These findings expand knowledge of potential risk factors related to readmissions. Future interventions to reduce hospital readmissions may focus on the aforementioned high-risk patient groups.